ANALISIS HUKUM TERHADAP UPAYA PENCEGAHAN DAN DETEKSI PENCUCIAN UANG DALAM BISNIS ASURANSI BNI LIFE (Studi Putusan Nomor 740/Pid.Sus/2014/PT MDN) - Nurul Qoedatul Khoiriyah Siregar; Mahmud Mulyadi; Abdul Aziz Alsa (Smart Education, 2026)
Abstract: Money laundering is a crime that can exploit various financial service sectors—including the insurance industry—as a means to disguise the origins of assets derived from criminal activity. The increasing complexity of insurance products and services heightens the risk of the sector being used as a vehicle for money laundering. This study aims to analyze efforts to prevent and detect money laundering within the insurance business, specifically focusing on Court Decision Number 740/Pid.Sus/2014/PT MDN, which involved a former agent of PT BNI Life Insurance Medan. The study employs a normative legal research method utilizing a statutory approach, supplemented by empirical data obtained through interviews. A descriptive-qualitative analysis was conducted on the relevant legislation, legal literature, and the court decision serving as the study's subject. The findings indicate that criminal acts in the insurance sector can take the form of insurance fraud, fraudulent claims, premium embezzlement, policy document forgery, and money laundering. In the case under review, the defendant was proven to have forged documents and misappropriated client investment funds, subsequently using those funds in a manner that disguised their origins. PT BNI Life Insurance’s efforts to prevent and combat money laundering are implemented through the application of